Multicolour photometry and Coravel observations of stars in the southern open cluster IC 2488 - Claria Olmedo, Juan Jose (2003)
We preseent new UBV photoelectric observations of 119 stars in the field of the southern open cluster IC 2488, supplemented by DDO and Washington photometry and Coravel radial velocities for a sample of red giant candidates. Nearly 50% of the stars sampled - including three red giants and one blue straggler - are found to be probable cluster members. Photometric membership probabilities of the red giant candidates show good agreement with those obtained from Coravel data. A mean radial velocity of (-2.63 +/- 0.06) km/s is derived for the cluster giants. The reddening across the cluster is found to be E(B-V) = 0.24 +/- 0.04. IC 2488, located at a distance of (1250 +/- 120) pc from the Sun and 96 below the Galactic plane, is most probably not related to the planetary nebulae ESO 166-PN21. A metal abundance 0.10 +/- 0.06 relative to the Sun is determined from DDO data of the red giant members, in good agreement with the metallicity values derived from five independent Washington abundance indices. An age of 180 Myr is determined from the fitting of isochrones computed with convective overshooting for Z = 0.019. The isochrone for log t = 8.25 reproduces remarkably well not only the morphology of the upper main sequence but also the observed red giant pattern.